Study and solutions guide to accompany Understandable statistics Brase/Brase - Farber, Elizabeth (Boston : Houghton Mifflin, 1999)
This book is about: Getting started; Organizing data; Averages and variations; Elementary probability theory; The binomial distribution; ...
Keywords: Mathematics; Mathematical statistics; Mathematical statistics